Characterisation of Reference Materials for In Situ Rb‐Sr Dating by LA‐ICP‐MS/MS. Issue 4 (4th October 2022) - Jegal, Yujin; Zimmermann, Catherine; Reisberg, Laurie; Yeghicheyan, Delphine; Cloquet, Christophe; Peiffert, Chantal; Gerardin, Marie; Deloule, Etienne; Mercadier, Julien
Abstract : We present Rb and Sr mass fraction and 87 Sr/ 86 Sr isotope ratio measurement results for four reference materials (RMs) obtained from the Service d'Analyse des Roches et des Minéraux (SARM), Nancy, France: Mica‐Mg, Mica‐Fe, GL‐O and FK‐N. These four RMs have different chemical compositions spanning the range of those of most K‐bearing feldspars and micas, making them potential calibration materials for in situ Rb‐Sr dating of natural minerals by LA‐ICP‐MS/MS. Selected grains and flakes from the four RMs present variable degrees of heterogeneity observable by SEM‐EDS and EPMA imaging, and chemical mapping. This heterogeneity is mainly related to inclusions of minerals within flakes and grains and to chemical substitutions linked to crystallographic control and alteration processes. The Mica‐Mg RM is the least affected. The powders available at the SARM were analysed by ID‐TIMS ( 87 Sr/ 86 Sr and Sr) and ID‐MC‐ICP‐MS (Rb) after digestion and separation. The mean 87 Rb/ 86 Sr ratios are 155.6 ± 4.7% (2 s, as for other RMs) for Mica‐Mg, 1815 ± 14% for Mica‐Fe, 36.2 ± 11% for GL‐O and 69.9 ± 5.9% for FK‐N. The mean 87 Sr/ 86 Sr ratios are 1.8622 ± 0.36% (2 s, as for other RMs) for Mica‐Mg, 7.99 ± 13% for Mica‐Fe, 0.75305 ± 0.12% for GL‐O, and 1.2114 ± 0.17% for FK‐N. The four RMs each show dispersion in 87 Sr/ 86 Sr and Rb and Sr mass fractions, to degrees that differ between RMs and that reflect the heterogeneity of their original crystals. The most heterogeneous RMs are GL‐O and Mica‐Fe. The calculated mean Rb‐Sr isotopic ages are 521 ± 24 Ma for Mica‐Mg, 287 ± 55 Ma for Mica‐Fe, 89.2 ± 9.9 Ma for GL‐O and 512 ± 30 Ma for FK‐N. The proposed age for Mica‐Fe may be unreliable due to the elevated dispersion of individual analysis linked to the highly radiogenic composition of the biotite and to the presence of numerous mineral inclusions. We recommend use of these proposed working values of 87 Sr/ 86 Sr and 87 Rb/ 86 Sr ratios and associated uncertainties when using the four RMs for in situ Rb‐Sr dating by LA‐ICP‐MS/MS. The availability of these four well‐characterised RMs will allow progress in the development and application of the Rb‐Sr dating approach by LA‐ICP‐MS/MS. Key Points: Mica‐Mg, Mica‐Fe, GL‐O and FK‐N were characterised as potential reference materials for in situ Rb‐Sr measurements by LA‐ICP‐MS/MS. Rb/Sr and Sr isotopic ratios of the four RMs were determined by isotope dilution TIMS and MC‐ICP‐MS. The RMs present Rb/Sr isotopic heterogeneity, which potentially needs to be tested by LA‐ICP‐MS/MS for their use as calibration materials.